The kiss quotient : a novel - Hoang, Helen (New York : A Jove Book, 2018)
A heartwarming and refreshing debut novel that proves one thing: there's not enough data in the world to predict what will make your heart tick. Stella Lane thinks math is the only thing that unites the universe. She comes up with algorithms to predict customer purchases--a job that has given her more money than she knows what to do with, and way less experience in the dating department than the average thirty-year-old. It doesn't help that Stella has Asperger's and French kissing reminds her of a shark getting its teeth cleaned by pilot fish.
Keywords: ESCORT SERVICES